Diffuse alveolar hemorrhage due to Legionella pneumophila serogroup 3 - Arnab Chowdhury (Journal of Community Hospital Internal Medicine Perspectives, 2020)
Legionella pneumophilia remains an important cause of pneumonia that can cause substantial clinical morbidity and mortality.Â We describe a case involving a 67-year-old woman with legionella pneumonia who developed diffuse alveolar hemorrhage. We also highlight the pitfalls of commonly used legionella urine antigen testing. Furthermore, we explore the role of high-dose steroid therapy as a treatment option for patients with diffuse alveolar hemorrhage secondary to legionella pneumoniaÂ who continue to deteriorate in spite of adequate antimicrobial therapy.